Controlling groundwater pollution from agricultural nonpoint sources: An overview of policy instruments - Cesare Dosi; Naomi Zeitouni (Fondazione Eni Enrico Mattei (FEEM), 2000)
The aim of this paper is to provide a review of policy instruments aimed at controlling pollution from agricultural diffuse sources, and compare their pros and cons. The review also includes a description of instruments introduced through recent reforms of the European Common Agricultural Policy (CAP), reforms aimed, inter alia, at integrating environmental protection into policies traditionally designed to achieve other objectives. The major results of this review may be summarised as follows. Firstly, a major barrier to the implementation of effective policy measures is the lack of information about the nature, extent, and social costs of groundwater pollution from agricultural diffuse sources. Secondly, policies aimed at controlling pollution from agricultural sources have usually relied, and still largely rely upon what is often referred to as "voluntarism", but which can probably be better described as a "soft-persuasion-though-subsidisation" approach. Besides being in contrast with the polluter pays ethics dominating other environmental policies, this approach has not brought about a significant and widespread reversal of pollution trends. Finally, there is a need for clearer policy framework specifying the principle for a division of labour between CAP and environmental policy provisions, and between payments and regulation related to positive and negative externalities of agricultural production.
Keywords: Q25; Q18; Q28; 330; Groundwater pollution; nonpoint sources; agricultural policy; environmental policy; Umweltpolitik; Gewässerbelastung; Landwirtschaft; EU-Agrarpolitik; EU-Staaten